2022
DOI: 10.3389/fimmu.2022.963111
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative neutrophil-lymphocyte ratio predicts unfavorable outcome of acute ischemic stroke patients who achieve complete reperfusion after thrombectomy

Abstract: PurposeOnly approximately half of anterior circulation large vessel occlusion (LVO) patients receiving endovascular treatment (EVT) have a favorable outcome. The aim of this study was to explore the association of dynamic inflammatory markers (i.e., neutrophil to lymphocyte ratios, NLR, measured at different times after EVT) as well as other potential influencing factors with unfavorable outcome among acute ischemic stroke (AIS) patients who achieved complete reperfusion after EVT.MethodsPatients treated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(35 citation statements)
references
References 36 publications
0
35
0
Order By: Relevance
“…The inflammatory mediators, cytokines, adhesion molecules, and chemokines released by immune inflammatory cells exacerbate tissue damage. According to previous studies, IR can be activated immediately after stroke event has occurred and is associated with poor prognosis ( 22 24 ). The mentioned mechanisms explain why the biomarkers now being researched are based on numerous inflammatory variables linked to stroke.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…The inflammatory mediators, cytokines, adhesion molecules, and chemokines released by immune inflammatory cells exacerbate tissue damage. According to previous studies, IR can be activated immediately after stroke event has occurred and is associated with poor prognosis ( 22 24 ). The mentioned mechanisms explain why the biomarkers now being researched are based on numerous inflammatory variables linked to stroke.…”
Section: Discussionmentioning
confidence: 91%
“…The inflammatory mediators, cytokines, adhesion molecules, and chemokines released by immune inflammatory cells exacerbate tissue damage. According to previous studies, IR can be activated immediately after stroke event has occurred and is associated with poor prognosis (22)(23)(24).…”
Section: Discussionmentioning
confidence: 94%
“…Several studies have shown that NLR as a dynamic variable is associated with HT ( 15 , 16 ), sICH ( 15 , 19 , 40 , 42 , 71 , 75 ), 3-month PFO ( 16 , 19 , 38 , 40 , 42 , 51 , 58 , 63 , 71 , 75 , 76 ), and death ( 19 , 38 , 58 , 63 , 71 ) in patients with AIS after IVT or EVT. These studies also showed that the post-treatment NLR has a more strong predictive ability for the poor prognosis of patients with AIS after reperfusion therapy than admission.…”
Section: Discussionmentioning
confidence: 99%
“…Another analysis demonstrated that an early increase in body temperature within 24 hours after EVT was associated with sICH and worse long term outcomes [ 34 ]. Neutrophil-lymphocyte ratio may be yet another novel predictor of outcome after EVT that requires further study [ 35 ]. Other imaging features, such as percent insular ribbon infarction, may also play a role in understanding infarct growth and long term outcomes [ 36 ].…”
Section: Discussionmentioning
confidence: 99%